We need targeted policy interventions in the EU to save soil carbon - Mäkipää, R.; Bruun, O.; Lehtonen, A.; Peltoniemi, M.; Kulovesi, K. (Frontiers in Environmental Science, 2024)
Globally, annual emissions from managed organic soils accounts for up to 5% of all anthropogenic greenhouse gas (GHG) emissions. Climate-wise management and restoration of degraded organic soils could reduce GHG emissions quickly and at relatively low costs. The European Union (EU) Member States that have large areas of organic soils with high GHG emissions are Sweden, Finland, Germany, Ireland, Poland, Netherlands, and the Baltic countries. To meet the climate targets and objectives of the Paris Agreement the land-use sector is indispensable and mitigation policies targeting organic soils will be needed. The international regulatory framework is broad and quite unspecific. In contrast, the European Union has initiated binding regulation for the land-use sector through the EU Climate Law, the EU LULUCF regulation, and the proposed EU Nature Restoration Law. However, even this regulatory approach is not on track to deliver on its binding ambitions, indicating the need for more effective implementation measures also on organic soils in the EU and its member states. Furthermore, we argue that appropriate policy selection should consider current knowledge regarding the climate impacts of management options of organic soils. Lastly, we need more studies on GHG emissions, and standardized methods for GHG inventories, to resolve uncertainties surrounding the impacts of management to GHG emissions. Successful policy implementation requires more efforts but also improved scientific justification through continuous consideration of climate policy integrity and strengthening of the reliability of GHG inventories.